Strategic Marketing Objectives in Mergers and Acquisitions in the Greek Food Industry - Panigyrakis, George G. (My University, 1994)
The purpose of this study is to provide empirical evidence of the effect of the type of ownership (foreign vs. domestic deals) on the objectives of corporate acquisitions in the Greek food industry, by reviewing the current literature and then analyzing a selected group of recent takeovers. In order to determine whether or not any effect did in fact exist, a set of twenty acquiring objectives were used on a number of possible strategic, marketing, financial and managerial goals. Analysis of these data indicated that, contrary to what would be expected from previous research Greek food mergers differ according to the nature of the deal (domestic vs. foreign).
Keywords: Mergers and acquisitions; Mergers; Announcement returns